Renewable Energy Consumption and Economic Growth Nexus—A Systematic Literature Review - Bhuiyan, Miraj Ahmed; Zhang, Qiannan; Khare, Vikas; Mikhaylov, Alexey; Pinter, Gabor; Huang, Xiaowen (Frontiers in Environmental Science, 2022)
As renewable energy emits no or low greenhouse gases, more countries are trying to increase the use of energies from renewable sources. At the same time, no matter developed or developing, nations have to maintain economic growth. This paper aims to systematically review the consumption nexus of renewable energy and economic growth. A total of 46 articles has been reviewed following the PRISMA guidelines from the year 2010-2021. Our review research shows that renewable energy does not hinder economic growth for both developing and developed countries. Whereas, there is little significance of consuming renewable energy (threshold level) on economic growth for developed countries.